2012
DOI: 10.1002/prep.201200060
|View full text |Cite
|
Sign up to set email alerts
|

Burning Characteristics of Ammonium Nitrate‐based Composite Propellants Supplemented with MnO2

Abstract: is found to be 4 %. The increasing ratio with x is virtually independent of the burning pressure and the AN content. However, the pressure exponent unfortunately increased by addition of MnO 2 . The apparent activation energy of the thermal decomposition for AN and the propellant is decreased by addition of MnO 2 . From thermal decomposition kinetics it was found that MnO 2 could accelerate the thermal decomposition reaction of AN in the condensed phase, and therefore, the burning characteristics of the AN-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The increase in the burning rate upon the addition of the catalyst was enhanced with increasing pressure. Furthermore, it increased with increasing AN content, because these catalysts improve the thermal decomposition of AN and=or the reaction of the decomposition gases of AN and the binder [9,11], and the mass fraction of AN in the propellant increases with increasing oxidizer content. As described above, the burning rate of the propellant with Fe 2 O 3 and the bicatalyst at 80% AN had its peak at n of 0.8, because the catalytic effect decreased with increasing n as the mass fraction of AN in the propellant decreases, whereas the effect of the replacement by RDX increased.…”
Section: Burning Rates Of An=rdx-based Propellants Supplemented With mentioning
confidence: 97%
See 2 more Smart Citations
“…The increase in the burning rate upon the addition of the catalyst was enhanced with increasing pressure. Furthermore, it increased with increasing AN content, because these catalysts improve the thermal decomposition of AN and=or the reaction of the decomposition gases of AN and the binder [9,11], and the mass fraction of AN in the propellant increases with increasing oxidizer content. As described above, the burning rate of the propellant with Fe 2 O 3 and the bicatalyst at 80% AN had its peak at n of 0.8, because the catalytic effect decreased with increasing n as the mass fraction of AN in the propellant decreases, whereas the effect of the replacement by RDX increased.…”
Section: Burning Rates Of An=rdx-based Propellants Supplemented With mentioning
confidence: 97%
“…The weight mean diameter of MnO 2 was 62 mm, as determined from the SEM photographs. The catalysts were added to a concentration of 4% relative to the propellant, because this value has previously been found to be the most effective for increasing the burning rate [9,11]. The burning characteristics of the AN-based propellant were improved by combining catalysts with differing catalytic mechanisms instead of supplementing the propellant with a single catalyst [11].…”
Section: Materials and Propellant Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the mesoporous β-MnO 2 is very effective in catalysing decomposition of AP (reducing the decomposition temperature by 153 °C with 2 wt.% catalyst). Naya et al [20] studied ammonium nitrate(V) (AN)-HTPBbased composites supplemented with MnO 2 as a burning catalyst and found that MnO 2 improves the burning characteristics of AN-based propellants. In other work, mixed oxides of copper, chromium, manganese, etc.…”
Section: Introductionmentioning
confidence: 99%
“…There are AN-based propellants described that contain polyurethanes (PU) [22]. Other important factors for the formation of propellant grains are burning rate modifiers and plasticizers [23].…”
Section: Introductionmentioning
confidence: 99%